Analisis SWOT Dalam Menentukan Strategi Kursus Dan Pelatihan Studi Pada LKP Sunakis Institute Di Bekasi - Sunarni Sunarni (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
In the era of globalization and intense business competition, human resource development has become the key to achieving sustainable business success and growth. Courses and training play a crucial role in enhancing the abilities of individuals and groups, aiding in the adaptation to business changes. This article analyzes the Sunakis Institute, a training center in Bekasi, through SWOT analysis to determine strategies for course and training development. The research employs a qualitative approach, with data gathered from literature, observations, interviews, and questionnaires. The results of the SWOT analysis reveal the strengths, weaknesses, opportunities, and threats of the Sunakis Institute. Strengths encompass a comprehensive curriculum and quality instructors, while weaknesses involve limited program variations and resources. Opportunities include high industry demand and industrial growth in Bekasi, while threats consist of intense competition and regulatory changes in education. The implications point toward the need for the Sunakis Institute to develop innovative programs, diversify its offerings, engage in industry collaborations, integrate technology, monitor regulations, and implement effective marketing. In formulating development strategies, the Sunakis Institute should leverage its strengths and opportunities, while prudently addressing weaknesses and threats.